2014
DOI: 10.19030/jabr.v30i4.8668
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Intrinsic And Extrinsic Religiosity On Attitudes Toward Products: Empirical Evidence Of Value-Expressive And Social-Adjustive Functions

Abstract: Religiosity affects various aspects of consumer behavior. This research distinguishes two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 34 publications
6
58
0
3
Order By: Relevance
“…Intrinsically religious consumers do not seek social approval due to their religiosity suppressing their value‐expressive needs. Moreover, they have less need for both consumer and luxury‐based products as a form of self‐expression, fulfilment, identity or social‐adjustive attitude (Pace, ). Based on these considerations, we formulated our first hypothesis as follows:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Intrinsically religious consumers do not seek social approval due to their religiosity suppressing their value‐expressive needs. Moreover, they have less need for both consumer and luxury‐based products as a form of self‐expression, fulfilment, identity or social‐adjustive attitude (Pace, ). Based on these considerations, we formulated our first hypothesis as follows:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Intrinsic and extrinsic religiosity, therefore, have different effects on the attitudes of consumers and on a number of consumer variables (Pace, 2014;Vitell et al, 2009). It has been shown that there is a strong relationship between intrinsic religiosity and attitudes towards ethical behaviour, while extrinsic religiosity tends not to be significantly related-or in a very limited way-to attitudes regarding ethical consumption (Angelidis & Ibrahim, 2004;Cottone, Drucker, & Javier, 2007;Vitell & Paolillo, 2003;Vitell et al, 2005).…”
Section: Religiositymentioning
confidence: 99%
“…The functional theory of attitudes was used to understand consumer attitudes in a variety of domains including: food with health claims (Žeželj, Milošević, Stojanović, & Ognjanov, 2012), store atmosphere (Kum, Bergkvist, Lee, & Leong, 2012), political consumerism (Gotlieb, 2015), consumer religiosity (Pace, 2014) and counterfeit purchase intention (Sharma & Chan, 2017). The relevance of the functional theory of attitude as a framework for understanding consumers attitudes was subject to various studies within the luxury literature (Bian & Forsythe, 2012;Halwani, 2020;Ioana-Daniela, Lee, Kim, Kang, & Hyun, 2018;Kauppinen-Räisänen, Björk, Lönnström, & Jauffret, 2018;Schade, Hegner, Horstmann, & Brinkmann, 2016).…”
Section: The Functional Theory Of Attitudesmentioning
confidence: 99%